COVID-19 online learning challenges: Kazakhstan secondary schools case study - Nurgaliyeva, Saniya; Bolatov, Aidos; Abildina, Saltanat; Zeinolla, Saule; Kurbonova, Bakhtikhon; Kyyakbayeva, Ulbossyn (Frontiers in Education, 2024)
Background: The COVID-19 pandemic necessitated a rapid transition to online learning (OL) globally, posing significant challenges for educational systems. This study investigates the experiences of secondary school students in Kazakhstan, highlighting the adaptation processes, educational outcomes, and challenges faced during this shift. Methods: Data were collected through an online survey administered to 3,670 secondary school students across Kazakhstan, selected through convenience sampling. The survey comprised 21 questions using a combination of Likert-type scales and multiple-choice questions to capture students' demographic details, satisfaction levels, perceived difficulties, and academic performance changes during OL. Data validation was ensured by cross-referencing responses, descriptive statistics, T-tests, ANOVA, correlation analysis, and regression were employed to analyze the data and identify factors influencing students’ attitudes towards OL and the associated challenges. Results: The results revealed that satisfaction with OL was positively correlated with satisfaction with education in general and negatively correlated with the level of difficulty in OL (p<0.001). Rural students, while more satisfied with learning overall (p<0.001), were less satisfied with OL compared to their urban peers, and also reported greater challenges (p<0.05). A significant portion of respondents (44.2%) disagreed that OL was an effective learning method, and 43.7% expressed a need for face-to-face interaction with teachers, especially female and rural students (p<0.001). Most students (40.8%) reported worse learning outcomes with OL, particularly urban students (p<0.001), and 32.0% noted a decrease in motivation. Regression analysis identified older students and those who experienced greater difficulty with OL as less likely to prefer it, while those who showed improvement in academic performance and motivation were more favorable towards OL. These findings highlight the complexity of educational preferences and the disparities between urban and rural students during the pandemic. Conclusion: While the findings may be applicable to other countries with similar educational systems, cultural, economic, and technological differences should be considered when generalizing the results. The insights gained from this study will be valuable for policymakers, educators, and academic institutions to improve the resilience and effectiveness of educational practices in the face of such challenges.